Re-assessment of the mid to late Quaternary glacial and environmental history of the Boco Plain, western Tasmania. (15th March 2017) - Augustinus, Paul; Fink, David; Fletcher, Michael-Shawn; Thomas, Ian
Abstract: The glacial geomorphology and drill core-based stratigraphy of the Boco Plain, western Tasmania, reveal a complex sequence of Quaternary glacial and non-glacial episodes. The upper part of the southern Boco Plain stratigraphy was previously dated by 14 C and U-series on interbedded organics of MIS 1 to MIS 5 affinity. U-series dating of ferricretes associated with glacial diamictons from Boco Plain cores suggested that there were glacial advances broadly correlative with MIS 6, 8 and ≥10. However, terrestrial cosmogenic nuclide ( 10 Be and 26 Al) exposure ages for the moraine sequence preserved on the wider Boco Plain area indicate that moraines previously attributed to MIS 6 and 8 advances were deposited during MIS 10 or earlier cold stages. There is no evidence for MIS 2, 4 or 6 affinity glacial advances onto the Boco Plain with ice of this age restricted to the West Coast Range. New palynological records from the Boco Plain core 6690 confirmed the late Quaternary ages of the upper part of the sequence, whilst extinct palynomorphs indicate a pre-Quaternary age for the glacial diamictons at the base of core Boco 4 and 10. Consequently, the mid-Pleistocene glacial sequence preserved in the Boco Plain is significantly older than previously envisaged, with the post MIS 10 to 12 geomorphology of the plain dominated by fluvial deltaic, swamp peat and lacustrine environments. Highlights: 10 Be dating of the Boco Plain moraines produced an age range spanning MIS 10 to 12. The age of the last glacier advance into the Boco basin was revised from MIS 6 to 10. The overdeepened basins have been filled with a range post-glacial sediments. The Boco Plain contains paleolake sequences spanning MIS 10 to the Holocene.